2020
DOI: 10.3390/antibiotics9070378
|View full text |Cite
|
Sign up to set email alerts
|

Risk Perceptions of Antibiotic Usage and Resistance: A Cross-Sectional Survey of Poultry Farmers in Kwara State, Nigeria

Abstract: Overwhelming empirical evidence has highlighted the contribution of indiscriminate antibiotic usage (ABU) in food animals to the overall burden of antibiotic resistance (ABR) in humans, thus making antibiotic use the main selective pressure driving antibiotic resistance. The social and behavioral perspective on antibiotic use and resistance in poultry is limited. Our study therefore aimed at obtaining information on antibiotic usage, awareness of ABR, and the attitude and perceptions towards prudent an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 28 publications
10
26
0
2
Order By: Relevance
“…It has also been described to BPS pig farmers, that presents low training on animal raising, with low knowledge on AM, engaging in several irrational AM use practices ( 97 ). Surface of the BPS, measure on acres, can be a proxy of flock size or total number of animals raised in the production systems, as previously reported ( 98 ), unit size as been reported as an element of inclusion for surveillance of AM usage in animal production from low and middle-income countries ( 99 ).…”
Section: Discussionmentioning
confidence: 97%
“…It has also been described to BPS pig farmers, that presents low training on animal raising, with low knowledge on AM, engaging in several irrational AM use practices ( 97 ). Surface of the BPS, measure on acres, can be a proxy of flock size or total number of animals raised in the production systems, as previously reported ( 98 ), unit size as been reported as an element of inclusion for surveillance of AM usage in animal production from low and middle-income countries ( 99 ).…”
Section: Discussionmentioning
confidence: 97%
“…Manure and other animal waste, as well as wastewater from farms, could be contaminated with antibiotics, their metabolites and resistant strains of bacteria [ 95 , 96 , 97 ]. Their improper disposal could also contaminate food sources, further propagating their resistance [ 96 , 98 , 99 ]. A survey found that roughly half of Italian veterinarians working on pig and cattle farms considered antimicrobial usage as not always in line with the guidelines [ 100 ].…”
Section: Antimicrobial Stewardship In Community Pharmacymentioning
confidence: 99%
“…However, they seemed to be underutilized, as the farmers in those countries did not seek their advice about antibiotic choice, dosage or use [ 97 , 103 ]. Especially useful could be the pharmacists’ role as educators, as farmers are often aware of their overuse of antibiotics, or the existence of antimicrobial resistance, but still continue with their practice as they do not know its consequences on public health or alternative methods to prevent diseases [ 96 , 98 , 103 , 106 ]. Another concerning practice was discovered by a study in India where the veterinary antimicrobial medications for working animals were dispensed intentionally in wrong dosages and in higher quantities for financial gain [ 105 ].…”
Section: Antimicrobial Stewardship In Community Pharmacymentioning
confidence: 99%
“…Tingkat pengetahuan resistansi antibiotik secara signifikan berhubungan dengan persepsi peternak, tetapi pengetahuan tidak berhubungan dengan sikap penggunaan antibiotik dan resistansi antibiotik (Al-Mustapha et al, 2020). Pengetahuan, sikap, dan khususnya praktik sangat bervariasi di berbagai negara.…”
Section: Hubunganunclassified